HUBUNGAN PERSEPSI TENTANG PELAYANAN PRIMA TERHADAP KEPUASAN PASIEN DI PUSKESMAS SUMBUL KABUPATEN DAIRI TAHUN 2018 - Diana Sinulingga; Elmina Tampubolon; Jon Piter Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2018)
ABSTRACT The development of health services, especially in health community centers was made health care quality in health community centers was easily overlooked. This study aims to analyze the relationship between patient satisfaction based on responsiveness, assurance, reliability, empathy and tangiable variables with the quality of service in the Sumbul health center in Dairi district. The study population was 69 respondents. The method used in this study is cross sectional, using analytical survey methods, and using a questionnaire for data collection. Data were analyzed by chi square test. Data using univariate and bivariate analysis. The results showed that there was a significant relationship between perceived reliability (p=0,000), responsiveness (p=0,000), assurance (p=0,000), empathy (p=0,000), and tangiable (p=0,000). So it can be concluded that there is a relationship between the variable responsiveness, assurance, reliability, empathy and tangiability with patient satisfaction Sumbul community health center Dairi district in 2018.